Clinical influence of switching companion diagnostic tests for EGFR‐TKs from Therascreen to Cobas v2. Issue 6 (2nd February 2021) - Uchibori, Ken; Takano, Natsuki; Manabe, Ryo; Tsugitomi, Ryosuke; Ogusu, Shinsuke; Tozuka, Takehiro; Sakamoto, Hiroaki; Yoshida, Hiroshi; Amino, Yoshiaki; Ariyasu, Ryo; Kitazono, Satoru; Yanagitani, Noriko; et al.
Abstract: Background: Several companion diagnostic (CDx) tests for epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) have been approved. In our institute, the CDx test for EGFR‐TKIs was changed from the Therascreen test (Therascreen) to the Cobas EGFR v2 test (Cobas) because only Cobas was approved for the use of osimertinib in patients with EGFR ‐mutated non‐small cell lung cancer (NSCLC) with T790M mutations. The clinical influence of switching the CDx test has not yet been examined comprehensively. Methods: All serial patients with lung cancer tested for EGFR mutations with CDx tests between February 2014 and February 2016 at the Cancer Institute Hospital of the Japanese Foundation for Cancer Research (JFCR) were enrolled in this analysis. Results: Therascreen was used as a CDx test for EGFR‐TKI therapy in 607 patients between February 2014 and January 2015, and Cobas was used in 621 patients between February 2015 and February 2016. EGFR mutations were detected in 218 patients (35.9%) and 244 patients (39.3%) tested with Therascreen and Cobas, respectively. At the initial diagnosis, 400 and 459 patients were tested with Therascreen and Cobas, respectively. EGFR mutation subtypes, including del19, L858R, and others, were detected in 13.0%, 17.0%, and 2.5% of patients using Therascreen and 17.4%, 14.4%, and 1.5% of patients using Cobas, respectively. Conclusions: No significant impact of switching from Therascreen to Cobas as the CDx test for EGFR mutations in clinical practice was observed. However, the detection pattern of the EGFR mutation subtypes between the two CDx tests was slightly different. Key points: Significant findings of the study: We examined the influence of changing the EGFR test in 1228 patients in total. The detection rate of EGFR mutations was similar. However, the detection pattern for EGFR subtype mutations was slightly different between the two tests. What this study adds: Switching CDx tests from target polymerase chain reaction (PCR)‐ to next‐generation sequencing (NGS)‐based methods may lead to obvious changes in clinical practice. When the CDx test is required to change, the investigation of this influence is warranted in future studies. Abstract : We examined the influence of changing the EGFR test among target PCR methods in 1228 patients in total. The detection rate of EGFR mutations was similar while the detection pattern for EGFR subtype mutations was slightly different between the two tests. In the future, switching companion diagnostic (CDx) tests from target PCR methods to NGS‐based methods may lead to obvious changes in clinical practice.